Dignitaries-Miscellaneous-0009
Front row: Guild, L.A.; Harton, Fresno; Burkman, State Dep't of Ed.; Tidyman, Fresno; Mosher, San Jose; Brown, Long Beach; Bratton, Long Beach. Back row: Roberts Sacramento; Enochs, San Francisco; McCollom, San Diego; Humboldt; Smith, Fresno; Prindiville, Los Angeles; Morris, Chico; Philbi, Cal Poly.